Destined for (un)happiness: Does childhood predict adult life satisfaction? - Paul Frijters; David W. Johnston; Michael A. Shields (Institute for the Study of Labor (IZA), 2011)
In this paper we address the question of how much of adult life satisfaction is predicted by childhood traits, parental characteristics and family socioeconomic status. Given the current focus of many national governments on measuring population well-being, and renewed focus on effective policy interventions to aid disadvantaged children, we study a cohort of children born in a particular week in 1958 in Britain who have been repeatedly surveyed for 50 years. Importantly, at four points in their adult lives this cohort has been asked about their life satisfaction (at ages 33, 42, 46, and 50). A substantive finding is that characteristics of the child and family at birth predict no more than 1.2% of the variance in average adult life satisfaction. A comprehensive set of child and family characteristics at ages 7, 11 and 16 increases the predictive power to only 2.8%, 4.3% and 6.8%, respectively. We find that the conventional measures of family socioeconomic status, in the form of parental education, occupational class and family income, are not strong predictors of adult life satisfaction. However, we find robust evidence that non-cognitive skills as measured by childhood behavioural-emotional problems, and social maladjustment, are powerful predictors of whether a child grows up to be a satisfied adult. We also find that some aspects of personality are important predictors. Adding contemporaneous adulthood variables for health and socio-economic status increases the predictability of average life satisfaction to 15.6%, while adding long-lags of life satisfaction increases the predictive power to a maximum of 35.5%. Repeating our analyses using data from the 1970 British Cohort Study confirms our main findings. Overall, the results presented in the paper point to average adult life satisfaction not being strongly predictable from a wide-range of childhood and family characteristics by age 16, which implies that there is high equality of opportunity to live a satisfied life, at least for individuals born in Britain in 1958 and 1970.
urn:nbn:de:101:1-201107042687
Keywords: I1; J1; 330; childhood; socioeconomic status; life satisfaction; non-cognitive; cognitive